2006
DOI: 10.1080/09540120500428952
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in attitudes toward AIDS clinical trials among urban HIV-infected individuals from racial and ethnic minority backgrounds

Abstract: Racial/ethnic minorities and women are under-represented in AIDS clinical trials (ACTs). We examined gender differences in willingness to participate in ACTs among urban HIV-infected individuals (N = 286). Sixty percent of participants were male, and most were from racial/ethnic minority backgrounds (55% African-American, 34% Latino/Hispanic, 11% White/other). Knowledge of ACTs was poor. Males and females did not differ substantially in their distrust of AIDS scientists, or in barriers to ACTs. Almost all (87%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Enrollment in a clinical trial is a process that requires active roles by both patients and researchers at multiple steps, from the potential participant’s awareness and intention to join a study to the researcher’s function as an unbiased enrollment facilitator for all possible participants. 8,10,11,12 In our data, the underrepresentation of racial minorities was evident at all levels of the research participation continuum: knowledge of trials, intention to participate, being approached by research team, effort to enroll, and successful enrollment. Our findings are consistent with results from a CDC-based study by Sullivan, et al, which found an OR of 0.6 for trial participation in black and Hispanic men compared to white men among 5,010 interviewees in 15 US states.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Enrollment in a clinical trial is a process that requires active roles by both patients and researchers at multiple steps, from the potential participant’s awareness and intention to join a study to the researcher’s function as an unbiased enrollment facilitator for all possible participants. 8,10,11,12 In our data, the underrepresentation of racial minorities was evident at all levels of the research participation continuum: knowledge of trials, intention to participate, being approached by research team, effort to enroll, and successful enrollment. Our findings are consistent with results from a CDC-based study by Sullivan, et al, which found an OR of 0.6 for trial participation in black and Hispanic men compared to white men among 5,010 interviewees in 15 US states.…”
Section: Discussionmentioning
confidence: 57%
“…mistrust from African-American community, language barriers in Hispanic immigrants). 4,6,7 Many of the studies that have evaluated the reasons that prevent minorities from enrolling in HIV/AIDS-related clinical trials have focused on a single site 1,8 or have studied populations with limited access to clinical trials. 4 Thus, there is a critical need for further research to understand the knowledge and attitudes that HIV-infected minorities in the US have towards participation in HIV/AIDS clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…However, we know relatively little about how minorities with HIV/AIDS view research, and even less is known about what can be done to foster participation of minority groups in HIV/ AIDS research, whether medical or behavioral. 6,8,13 HIV/AIDS continues to be a leading cause of illness and death in the United Sates and has had a notably disproportionate effect on racial and ethnic minority communities. 14 For example, in 2004, estimated HIV/AIDS case rates for blacks and Hispanics were 8.5 and 3.3 times higher, respectively, than rates for whites.…”
Section: Introductionmentioning
confidence: 99%
“…Additional descriptive factors are found in Table 1. Detailed information on other baseline characteristics including ACT knowledge and attitudes (such as willingness, distrust), and gender differences, are described elsewhere (Gwadz et al 2006). …”
Section: Discussionmentioning
confidence: 99%